2003
DOI: 10.1161/01.cir.0000068356.38592.68
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Embryonic Stem Cells to Cardiomyocytes

Abstract: Background-Cardiomyocytes derived from human embryonic stem (hES) cells could be useful in restoring heart function after myocardial infarction or in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
387
2
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 981 publications
(407 citation statements)
references
References 29 publications
13
387
2
5
Order By: Relevance
“…For the induction of specific cell lineages from ES cells, purified growth and/or differentiation factors or factorproducing feeder or stromal cells have been used (Chadwick et al, 2003;Cohen et al, 2007;Green et al, 2003;Kaufman et al, 2001;Kehat et al, 2001;Lavon et al, 2006;Levenberg et al, 2002;Mummery et al, 2003;Rambhatla et al, 2003;Sottile et al, 2003;Vodyanik and Slukvin, 2007;Zhang et al, 2001). In some cases, very complex culture strategies have been used, including the sequential addition and withdrawal of factors and purification of specific cell populations during the culture period (Fang et al, 2006;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For the induction of specific cell lineages from ES cells, purified growth and/or differentiation factors or factorproducing feeder or stromal cells have been used (Chadwick et al, 2003;Cohen et al, 2007;Green et al, 2003;Kaufman et al, 2001;Kehat et al, 2001;Lavon et al, 2006;Levenberg et al, 2002;Mummery et al, 2003;Rambhatla et al, 2003;Sottile et al, 2003;Vodyanik and Slukvin, 2007;Zhang et al, 2001). In some cases, very complex culture strategies have been used, including the sequential addition and withdrawal of factors and purification of specific cell populations during the culture period (Fang et al, 2006;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In hESC-differentiating multi-lineage aggregates (EBs), only a very small fraction of cells (< 4 %) spontaneously differentiate into cardiomyocytes [3,26]. Immune-selection, co-culturing, and morphogens have been used to isolate and enrich populations of immature cardiomyocytes from hESC-differentiating EBs [26,116119]. Enriched hESC-derived cardiomyocytes could generate small grafts and function as the biological pacemaker in animal infarcted models [27].…”
Section: Transform Pluripotent Human Embryonic Stem Cells Into Carmentioning
confidence: 99%
“…Moreover, visceral endoderm-like cells can induce the differentiation of the epiblast to undergo hematopoiesis and vasculogenesis and respecify prospective neuroectodermal cell fates [25]. Mummery et al previously demonstrated that coculture of hESC lines with visceral endoderm-like cells induce epithelia through formation of large cystic structures that stain positively for a-fetoprotein and are presumably extraembryonic layers [29]. Therefore, we propose that SD-hESCs are not just an artifact cell produced during in vitro hESC culture, but that they may represent an important intermediate cell state related to appropriate germinal layer formation in the ICM during human blastocyst development.…”
Section: Fig 5 Cystic Ebs and Noncysticmentioning
confidence: 99%